Supply & installation of MS railing (package 2) for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Retail Scape Limited to supply and installation of the MS railing for the Brac University new campus project.